One-way coupling between a CFD model and a transient thermal model of the human body - Senhorinha Teixeira (2014)
For the same environment, thermal perception varies with people and satisfaction with the occupational working place has a great influence on work performance and productivity. There are several methods for solving problems of thermal comfort, including computer simulation of the thermal system comprising the Human Body - Clothing Environment and also CFD (Computational Fluid Dynamics) techniques used to analyze the HVAC (Heating, Ventilating, and Air Conditioning) systems, particularly in the vicinity of the human body. In the current study, a CFD model was coupled with a thermoregulatory model of the human body to describe the fluid flow, heat and mass transfer between the ventilation air and a human manikin in-side a room. The computational model solves the heat, mass and momentum conservation equations in the computation domain using a finite volume discretization method in the ANSYS © environment. The results can later be used to calculate the PMV-PPD index.